The influence of electrocoagulation to the reduction of COD, BOD, and TSS of Batik Industry wastewater - Zuhria, Faida; Sarto, Sarto; Prasetyo, Imam (Centre for Science and Technology, IAIN Surakarta, 2018)
Despite of the positive effect of the growth of Batik industry in Yogyakarta to economy, the waste water pollution of dying process of Batik industry has negative impact to environment. Initial measurement of COD, BOD and TSS of waste water resulted from dying process of Batik that implemented Naphtolat and Diazo Salts were exceeded the threshold. Hence, this study implemented electrocoagulation for processing Batik wastewater. The results showed that the range of the electrodes and the voltage are give effect to the reduction in COD, BOD, and TSS in liquid sewage electrocoagulation process in dye wastewater in batik industry